Forms And Functions Of Code-Mixing In Student Interactions During Academic Task Discussions - Dwi Ratna Swari; ⁠Hanum Zanuba Raihanah Salma; Abdul Kholiq (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Code-mixing is a common phenomenon among bilingual and multilingual speakers: a person inserts elements from another language into their speech, not because the situation demands it, but because it simply feels more fitting. This study examines the forms and functions of code-mixing in conversations among students of the Indonesian Language and Literature Education Study Program, Universitas Negeri Surabaya, particularly when they discuss academic assignments. Three questions guide this research: what forms of code-mixing appear, which type occurs most frequently, and what pragmatic functions it serves in informal academic discussions. The study employs a qualitative descriptive approach from a sociolinguistic standpoint, with data drawn from two naturally occurring conversation sessions through audio recording, observation, and field notes. The findings show that the most dominant form is inner code-mixing the insertion of Javanese elements into Indonesian speech broken down into word insertions (63%), phrase insertions (27%), and clause insertions (10%). Four pragmatic functions were identified: facilitating informal communication, marking group solidarity and identity, providing emphatic stress, and clarifying complex arguments. The conclusion is simple but significant: code-mixing is not evidence of limited language ability. In student discussions, it is a choice deliberate, purposeful, and effective.